Konstruksi Realitas Politik Hukum Indonesia dalam Podcast Bocor Alus Politik Tempo.Co - Sadiyah, Helni; Anshori, Dadang S.; Sastromiharjo, Andoyo (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The decline of democracy and the weakening of the law during the two periods of President Joko Widodo's administration became hot topics discussed by the mass media, including on the YouTube channel Bocor Alus Politik Tempodotco. This research aims to determine the construction of the reality of Jokowi era legal policy through a qualitative research approach of content analysis. Data in the form of text from transcripts of video recordings which were analyzed using Teun A. van Dijk's (1988) critical discourse analysis framework, covering three dimensions of discourse: text, social cognition, and social context. The data source was taken from the Youtube video Podcast Bocor Alus Politik episode Nilai Rocky Gerung untuk 10 Tahun Jokowi: Dinasti Politik dan Warisan Beban untuk Prabowo Subianto, which was broadcast on the Tempodotco Youtube channel on August 26 2024. The research results show that the text dimensions in the podcast use metaphorical and rhetorical language style to emphasize critical assessments of Jokowi's political and legal policy, highlighting the decline of democracy and the practice of political dynasties. The social cognition dimension represents knowledge about Jokowi's role as President who failed to implement democracy and hopes for Prabowo to restore democratic values. The social context dimension shows the role of mass media in influencing public opinion by creating space for critical discussion using digital media. This research recommends the need for further study regarding the role of digital media in building the construction of social reality in Indonesia, especially on social media platforms.